Optimizing Resident Charge Capture with Disappearing Help Text in Note Templates - Martin, Taylor B.; Bell, Douglas S.; Gornbein, Jeffrey A.; Lukac, Paul J. (Applied Clinical Informatics, 2025)
Objective This study aimed to assist residents in selecting the correct Current Procedural Terminology (CPT) code for evaluation and management (E/M) services through the addition of disappearing help text into a standardized note template.Methods We created a disappearing text block that summarizes E/M requirements and embedded it into the note template used by residents at a pediatric urgent care clinic. An intervention cohort composed of postgraduate year 1 (PGY 1) residents was instructed to use this note template, while senior residents (PGY 2–3) were instructed to use an identical template that lacked the help text. We evaluated the incidence of CPT change by the attending physician for each visit as a proxy for improvement in resident billing practices. Logistic regression with a primary outcome of whether the encounter CPT code was changed was completed.Results There were 2,869 encounters during the 255-day study period; the help text was used in 1,112 (38.8%) encounters. There was some crossover in note use; that is, PGY 1s used the note without help text and PGY 2s used the note with help text. Nevertheless, all residents who used the help text had a lower unadjusted rate of CPT change (22.1 vs. 30.6%, odds ratio [OR] = 0.64, p < 0.0001). This pattern persisted when stratified by trainee level—PGY 1 (22.6 vs. 45.3%, OR = 0.35, p < 0.0001) and PGY 2–3 (12.2 vs. 27.8%, p = 0.018). Adjusting for multiple factors, the use of help text was associated with a lower incidence of CPT change (OR = 0.28, 95% confidence interval [CI]: 0.19–0.44).Conclusion Residents' use of the disappearing help text was associated with a large decrease in CPT code adjustment by attending physicians, which demonstrates its promise for improved E/M coding and other applications.
Keywords: clinical decision support; ambulatory care/primary care; billing; process improvement; CPT; process management tools; professional training